We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
366
2
avatar

Let f(x) = (3x^2 - 10x - 25)/(x + 1) and g(x) = (3x^2 - 10x - 25)/(3x^2 + 11x + 10). Find the sum of all real numbers that are not in the domain of f(g(x)).

 

--

 

If you could give me the answer to this question quickly, that would be very helpful. Thanks!

 Jan 29, 2018

Best Answer 

 #1
avatar+8095 
+3

\(f(\,g(x)\,)\,=\,\frac{3(\,g(x)\,)^2-\,10(\,g(x)\,)\,-\,25}{g(x)\,+\,1}\)

 

 

f( g(x) ) is undefined when  g(x)  is undefined, and  g(x)  is undefined when...

 

3x2 + 11x + 10  =  0

 

3x2 + 6x + 5x + 10  =  0

 

3x(x +  2) + 5(x + 2)  =  0

 

(x + 2)(3x + 5)  =  0

 

x  =  -2    and   x  =  -5/3

 

f( g(x) )  is also undefined when 

 

g(x) + 1  =  0

 

\(\frac{3x^2-10x-25}{3x^2+11x+10}+1\,=\,0 \\~\\ \frac{3x^2-10x-25}{3x^2+11x+10}+\frac{3x^2+11x+10}{3x^2+11x+10}\,=\,0 \\~\\ \frac{6x^2+x-15}{3x^2+11x+10}\,=\,0\)

 

6x2 + x - 15   =   0

 

6x2 - 9x + 10x - 15   =   0

 

3x(2x - 3) + 5(2x - 3)   =   0

 

(2x - 3)(3x + 5)   =   0

 

x  =  3/2   and   x = -5/3

 

f(g(x))  is undefined when  x = -2 ,  x = -5/3 ,  and  x = 3/2  .

 

-2  +  -5/3  +  3/2   =   -13/6

 Jan 29, 2018
 #1
avatar+8095 
+3
Best Answer

\(f(\,g(x)\,)\,=\,\frac{3(\,g(x)\,)^2-\,10(\,g(x)\,)\,-\,25}{g(x)\,+\,1}\)

 

 

f( g(x) ) is undefined when  g(x)  is undefined, and  g(x)  is undefined when...

 

3x2 + 11x + 10  =  0

 

3x2 + 6x + 5x + 10  =  0

 

3x(x +  2) + 5(x + 2)  =  0

 

(x + 2)(3x + 5)  =  0

 

x  =  -2    and   x  =  -5/3

 

f( g(x) )  is also undefined when 

 

g(x) + 1  =  0

 

\(\frac{3x^2-10x-25}{3x^2+11x+10}+1\,=\,0 \\~\\ \frac{3x^2-10x-25}{3x^2+11x+10}+\frac{3x^2+11x+10}{3x^2+11x+10}\,=\,0 \\~\\ \frac{6x^2+x-15}{3x^2+11x+10}\,=\,0\)

 

6x2 + x - 15   =   0

 

6x2 - 9x + 10x - 15   =   0

 

3x(2x - 3) + 5(2x - 3)   =   0

 

(2x - 3)(3x + 5)   =   0

 

x  =  3/2   and   x = -5/3

 

f(g(x))  is undefined when  x = -2 ,  x = -5/3 ,  and  x = 3/2  .

 

-2  +  -5/3  +  3/2   =   -13/6

hectictar Jan 29, 2018
 #2
avatar+101090 
+1

Very nice, hectictar...!!!

 

cool cool cool

 Jan 29, 2018

17 Online Users

avatar
avatar